2019
DOI: 10.5897/ajbr2019.1033
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of invertase from Momordica charantia (bitter melon) by three phase partitioning (TPP) method

Abstract: The single step three-phase partitioning (TPP) method was evaluated for the purification of invertase from Momordica charantia. Optimum conditions for TPP method, that is, 70% ammonium sulfate saturation, 1:0.5 t-butanol ratio and 30 min incubation time lead to 20.28% efficiency and 10.48 fold partial purification. Total protein decreased from 34.86 mg to 0.68 mg in the homogenate, and the specific activity of the enzyme increased from 21.67 to 227.02 U/mg protein. The purified enzyme showed maximum activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The studies reported on the TPP method used for concentration and purification of proteases from Cucumismelo (Cucumisin) and Calotropis procera have also demonstrated high purification fold and activity recovery at 60%–65% salt saturation which is close to our findings in the present study (Gagaoua & Hafid, 2016; Rawdkuen et al, 2010). The study by Nihan et al on invertase extraction from bitter melon using the TPP method has also reported the highest purification fold and enzyme recovery at 70% (NH₄)₂SO₄ saturation (Nihan & Burku, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported on the TPP method used for concentration and purification of proteases from Cucumismelo (Cucumisin) and Calotropis procera have also demonstrated high purification fold and activity recovery at 60%–65% salt saturation which is close to our findings in the present study (Gagaoua & Hafid, 2016; Rawdkuen et al, 2010). The study by Nihan et al on invertase extraction from bitter melon using the TPP method has also reported the highest purification fold and enzyme recovery at 70% (NH₄)₂SO₄ saturation (Nihan & Burku, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Optimal conditions that resulted in higher invertase recovery in the purification procedure. (Nihan kubra Belligun and Burcu Saygideger Demir et al, 2019) [24] Invertase enzyme in the presence of surfactants is the next approach. This autolyzate was combined with 0.12 sodium picrate at a 1:0.35 ratio.…”
Section: A Nigermentioning
confidence: 99%